Prediction of Post-operative Survival of Colorectal Cancer Patient By Using the Prognostic Nutritional Index: An Evidence-Based Case Report - Nurul Ratna Manikam; Yosua Y Kristian; Luana Lidwina; Ayu Diandra Sari; Diana Sunardi (Indonesian Nutrition Association, 2019)
Background: Colorectal cancer patients may be treated with several modalities and one of them is surgical treatment. Surgery in cancer patients is risky procedure and may not always resulted in prolonged survival. Therefore, before receiving any recommended treatment, the patient’s prognosis has to be assessed and defined properly. Several methods are available to assess the prognosis of cancer patients; one of them is the prognostic nutritional index (PNI).Objective: This study aimed to predict the survival of a colorectal cancer patient post-operatively by calculating the pre-operative PNI score.Method: Literature searching was done using inclusion and exclusion criteria on two databases, i.e. the PubMed and the Cochrane Library. The outcome was survival (disease-free survival, relapse-free survival, or overall survival).Results: Five articles that address the clinical question were retrieved. All indicated that a patient with low PNI score (<44.5) had a shorter overall survival (HR between 1.92 and 3.98 with all p values were <0.05).Conclusion: Pre-operative PNI score can be used to assess the overall survival of a colorectal cancer patient who underwent surgical resection. Patients with a PNI score > 44.5 had better survival than lower PNI score.